Functional and Therapeutic Relevance of Rho GTPases in Innate Immune Cell Migration and Function during Inflammation: An In Silico Perspective - Pankaj Dipankar; Puneet Kumar; Shiba Prasad Dash; Pranita P. Sarangi (Hindawi Limited, 2021)
Systematic regulation of leukocyte migration to the site of infection is a vital step during immunological responses. Improper migration and localization of immune cells could be associated with disease pathology as seen in systemic inflammation. Rho GTPases act as molecular switches during inflammatory cell migration by cycling between Rho-GDP (inactive) to Rho-GTP (active) forms and play an essential role in the precise regulation of actin cytoskeletal dynamics as well as other immunological functions of leukocytes. Available reports suggest that the dysregulation of Rho GTPase signaling is associated with various inflammatory diseases ranging from mild to life-threatening conditions. Therefore, it is crucial to understand the step-by-step activation and inactivation of GTPases and the functioning of different Guanine Nucleotide Exchange Factors (GEFs) and GTPase-Activating Proteins (GAPs) that regulate the conversion of GDP to GTP and GTP to GDP exchange reactions, respectively. Here, we describe the molecular organization and activation of various domains of crucial elements associated with the activation of Rho GTPases using solved PDB structures. We will also present the latest evidence available on the relevance of Rho GTPases in the migration and function of innate immune cells during inflammation. This knowledge will help scientists design promising drug candidates against the Rho-GTPase-centric regulatory molecules regulating inflammatory cell migration.